Assessing the progression of chronic periodontitis using subgingival pathogen levels: a 24-month prospective multicenter cohort study. Issue 1 (December 2017) - Kakuta, E.; Nomura, Y.; Morozumi, T.; Nakagawa, T.; Nakamura, T.; Noguchi, K.; Yoshimura, A.; Hara, Y.; Fujise, O.; Nishimura, F.; Kono, T.; Umeda, M.; et al.
Abstract Background The diagnosis of the progression of periodontitis presently depends on the use of clinical symptoms (such as attachment loss) and radiographic imaging. The aim of the multicenter study described here was to evaluate the diagnostic use of the bacterial content of subgingival plaque recovered from the deepest pockets in assessing disease progression in chronic periodontitis patients. Methods This study consisted of a 24-month investigation of a total of 163 patients with chronic periodontitis who received trimonthly follow-up care. Subgingival plaque from the deepest pockets was recovered and assessed for bacterial content ofPorphyromonas gingivalis, Prevotella intermedia, andAggregatibacter actinomycetemcomitans using the modified Invader PLUS assay. The corresponding serum IgG titers were measured using ELISA. Changes in clinical parameters were evaluated over the course of 24 months. The sensitivity, specificity, and prediction values were calculated and used to determine cutoff points for prediction of the progression of chronic periodontitis. Results Of the 124 individuals who completed the 24-month monitoring phase, 62 exhibited progression of periodontitis, whereas 62 demonstrated stable disease. TheP. gingivalis counts of subgingival plaque from the deepest pockets was significantly associated with the progression of periodontitis (p < 0.001, positive predictive value = 0.708). Conclusions TheP. gingivalis counts of subgingival plaque from the deepest pockets may be associated with the progression of periodontitis.